2010
DOI: 10.5483/bmbrep.2010.43.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of KHG26377 on glutamate dehydrogenase activity in cultured islets

Abstract: GDH has been known to be related with hyperinsulinismhyperammonemia syndrome. We have screened new drugs with a view to developing effective drugs modulating GDH activity. In the present work, we investigated the effects of a new drug, KHG26377 on glutamate formation and GDH activity in cultured rat islets. When KHG26377 was added to the culture medium for 24 h prior to kinetic analysis, the Vmax of GDH was decreased by 59% whereas Km is not significantly changed. The concentration of glutamate decreased by 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…Green tea polyphenols inhibit GDH and reduce insulin release when pancreatic islets are stimulated with glutamine and BCH (2-amino-2-norbornane carboxylic acid), although not upon glucose stimulation (12). We previously reported the loss of GDH activity following perfusion of islets with KHG26377, a thiazole derivative, in vitro (22). KHG26377 also reduced the amount of insulin released and caused a rightward shift in the concentration dependence of glucose-induced insulin secretion in islets (22).…”
Section: Effects Of Khg26377 On Gdh Activity and Insulin Secretion Inmentioning
confidence: 99%
See 3 more Smart Citations
“…Green tea polyphenols inhibit GDH and reduce insulin release when pancreatic islets are stimulated with glutamine and BCH (2-amino-2-norbornane carboxylic acid), although not upon glucose stimulation (12). We previously reported the loss of GDH activity following perfusion of islets with KHG26377, a thiazole derivative, in vitro (22). KHG26377 also reduced the amount of insulin released and caused a rightward shift in the concentration dependence of glucose-induced insulin secretion in islets (22).…”
Section: Effects Of Khg26377 On Gdh Activity and Insulin Secretion Inmentioning
confidence: 99%
“…The N-and C-terminal regions of SIRT3 influence its activity against GDH and peptide substrates, indicating that these regions play roles in regulation and substrate recognition (21). Our recent study showed that KHG26377 (2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride) inhibits GDH activity and downregulates insulin secretion in pancreatic islets (22). However, its mechanisms of action have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride suppressed glutamate-induced excitotoxicity in rat glial cultures 5 and inhibited glutamate dehydrogenase activity in cultured islets. 6 As an extension of our efforts to investigate the biological activities of the analogues, we report here that 2-aminothiazole derivatives effectively suppress the lipopolysaccharide (LPS)-induced interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) level.…”
mentioning
confidence: 99%